PEMBINAAN ORGANISASI KELOMPOK USAHA MANDIRI MASYARAKAT (KUMM) BERBASIS AKUNTABILITAS DAN ISLAMI - Nurul Huda; Nazwirman Nazwirman; Hulmansyah Hulmansyah (Universitas Islam kalimantan MAB, 2017)
Sector Usaha Mikro Kecil dan mengengah (UMKM), in particular Micro is a business that is in desperate need of attention the government or society. Because there are huge numbers and can absorb a lot of labor. Community Service which is part of the efforts to develop micro approach to sharing and mentoring. The object of this Community Service is Business Usaha Mandiri Masyarakat (KUMM) are located in the districts of Tanjung Priok. Objective research provides knowledge and understanding of the entire board and management members on the basis of a business based on Islam and accountability. Mentoring to see the progress of the business. The result of activities carried out to make them satisfied and increased knowledge